UMKM DEVELOPMENT STRATEGY THROUGH THE DEVELOPMENT POLICY OF THE COOPERATION DEPARTMENT OF SIGI DISTRICT, CENTRAL SULAWESI - Syamdy, Inten Suweno Syamdy; Hasanuddin , Bakri; Fadjar, Adfiyani (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
The purpose of this analysis is to gain an understanding of the UMKM Development Strategy through the Development Policy of the Sigi Regency Cooperation and UKM Department in Central Sulawesi. This research was conducted in a qualitative descriptive manner using a process of observation, interviews and documentation. The data is then presented and analyzed using SWOT matrix analysis to identify strengths, weaknesses, opportunities and threats. The results of this research indicate that the strategy implemented to develop UMKM at the Sigi Regency Cooperation Department is appropriate and makes maximum use of the potential strengths possessed in seizing opportunities at the Sigi Regency Cooperation and UKM Department where the potential can be developed in the future and the results determining the coordinate points X; , Management of open information, improving the quality of work programs, developing financial institutions, increasing empowerment of UMKM, consider community needs and strengthen authority and autonomy.